Multiorgan Failure and Refractory Lactic Acidosis due to Pasteurella multocida Septicemia in a Patient with No Animal Exposure - Damaris Pena; Yaneidy Santana; Jose Perez Lara; Efrain Gonzalez; Misbahuddin Khaja (Case Reports in Infectious Diseases)
Introduction. Pasteurella multocida is a gram-negative coccobacillus pathogenic to animals. It can cause infection in humans by a bite, scratch, or lick from a cat or dog. P. multocida can cause a variety of infections in humans, including cellulitis, osteomyelitis, endocarditis, peritonitis, and septic shock. Case Presentation. A 56-year-old male presented to our hospital with a 2-day history of fever, abdominal pain, nausea, and vomiting. He denied exposure to cats, dogs or other pets. He had severe respiratory distress requiring ventilator support, profound septic shock requiring multiple vasopressors, severe lactic acidosis, and renal failure requiring emergent hemodialysis. Blood cultures confirmed the presence of P. multocida. The patient subsequently died of cardiopulmonary arrest due to multiorgan failure with refractory shock. Conclusion. P. multocida septicemia can lead to septic shock. Early identification of this organism may decrease mortality. Although our patient had no known cat or dog exposure, physicians should enquire about a history of animal exposure when a patient presents with an infection with no obvious cause.